"The History And Politics Of 'False Memories': The Australian Experience". Issue 2 (15th March 2022) - McMaugh, Kate; Middleton, Warwick
ABSTRACT: The Australian history of the false memory (FM) movement has similarities to that of the UK and America, but also important differences that are rarely described in the literature. This article, through an examination of cross-discipline professional literature, media reports, and the personal observations of the second author, describes the history of the FM Movement in Australia and outlines similarities and differences between Australia, the UK and America. All three countries experienced the establishment of false memory syndrome (FMS) societies and a backlash against those reporting or treating child sexual abuse (CSA). However, in Australia the backlash was notably smaller and led to a different trajectory for those reporting CSA, particularly institutional abuse. The authors propose that this is due to differences in the media and legal systems; the later timing of the backlash in Australia; and a more muted reporting of satanic ritual abuse (SRA), which avoided the extreme disbelief and backlash that occurred in other countries.